Conducting ethical economic research: Complications from the field - Alderman, Harold; Das, Jishnu; Rao, Vijayendra (Oxford University Press, 2017)
This chapter discusses practical issues confronted when conducting surveys as well as designing appropriate field trials. First, we look at the challenge of ensuring transparency while maintaining confidentiality. Second, we explore the role of trust in light of asymmetric information held by the surveyor and by the respondents as well as the latter’s expectations as to what their participation will set in motion. We present case studies relevant to both of these issues. Finally, we discuss the role of ethical review from the perspective of research conducted through the World Bank.